Understanding the Impact of the Psychological Cognitive Process on Student Learning Satisfaction: Combination of the Social Cognitive Career Theory and SOR Model - Zhang, Guihua; Yue, Xiaoyao; Ye, Yan; Peng, Michael Yao-Ping (Frontiers in Psychology, 2021)
In higher education, student learning satisfaction is a significant predictor of learning, which indicates students' commitment to learning and their future academic achievement. The study combines the social cognitive career theory and S-O-R model to explore the psychological cognition and attitude derived from students during their learning, discusses the pattern of student learning satisfaction enhancement from the aspect of process, and further understands the relationships among social support system, interaction relationship, self-efficacy, generic skills and learning satisfaction. In this study, 800 valid copies of questionnaire were collected from 12 universities in way of purposive sampling, and the structural model was analyzed by PLS-SEM. The results showed that the relationships among all the constructs were positive and showed a significant effect; furthermore, the research results showed that self-efficacy and student generic skills had a significantly indirect effect in the model, that is a mediating effect. Finally, corresponding theoretical and practical implications have been put forward based on the research results.